Numerical Simulation Applied in Identification of Roof Bed Separation for Mining Thick Coal Seam Under Nappe Structure. (January 2019) - Gui, Herong; Hu, Rongjie; Kang, Zhiyong; Qiu, Huili; Li, Jun
Abstract: In China coalmines, economic losses and human casualties inflicted by roof bed separation water have been acutely severe in recent years. This article takes the engineering case, mining thick coal seam under nappe, in Xinji No. 1 Coalmine in Huainan mining field. Given the low tensile strength of lower roof bed under large mining heights, numerical simulation is applied to No. 1307 fully mechanized top-coal caving (FMTC) working face by coupling elastoplastic finite element model (FEM) in rock mechanics with "no-tension analysis" (NTA) to map out, in the roof bed, pattern of stress distribution and the maximum heights of caving zone (37m) and of water-conductive fractured zone (98.5m), quantitatively delineating the location of bed separation. Specifically, bed separation F is the closest to the water-conductive fractured zone (by merely 1.93m) and of a maximum width of 6.4m, flagging a major threat to mining safety. These results are further corroborated by exploratory drills. Outcomes can be of reference to other coal-mining countries when identifying bed separation and treating related water hazards during mining under complex geological conditions.